Preparation method of oxidized sodium hyaluronate

By oxidizing sodium hyaluronate in water, combined with the use of sodium periodate and glycol, the problem of preparing oxidized sodium hyaluronate in the prior art was solved, high yield and process stability were achieved, and the potential of the material in anti-inflammatory and antioxidant was demonstrated.

CN119569909APending Publication Date: 2025-03-07WENDE XILIN (HANGZHOU) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411840074.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare high yield and process-stable oxidized sodium hyaluronate, especially in the application of anti-inflammatory or antioxidant.

Method used

By adding sodium hyaluronate to water and using sodium periodate as an oxidizing agent, the reaction was terminated with ethylene glycol, and the impurities were removed by ultrafiltration, finally obtaining oxidized sodium hyaluronate with the structural formula Mw/Mn<3.

Benefits of technology

The high yield and process stability of oxidized sodium hyaluronate are achieved, suitable for industrial production, and demonstrate the potential application of the material in anti-inflammatory and antioxidant aspects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569909A_ABST
    Figure CN119569909A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedicine, in particular to a preparation method of oxidized sodium hyaluronate. The preparation method of the oxidized sodium hyaluronate comprises the following steps: adding sodium hyaluronate into water, then adding a solution containing sodium periodate to carry out an oxidation reaction, adding ethylene glycol to terminate the reaction, and removing impurities, thereby obtaining the oxidized sodium hyaluronate. The molar ratio of the sodium hyaluronate to the sodium periodate is 1: (0.15-3.6). The method has the advantages of high yield and stable process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical technology, and in particular to a method for preparing oxidized sodium hyaluronate. Background Art

[0002] Hyaluronic acid is a disaccharide unit glycosaminoglycan composed of D-glucuronic acid and N-acetylglucosamine. Sodium hyaluronate is the sodium salt of hyaluronic acid, a linear macromolecular polysaccharide, and its cross-linked product is cross-linked hyaluronic acid, also known as hyaluronic acid. The structural formula of sodium hyaluronate is as follows:

[0003]

[0004] Sodium hyaluronate acts as a tissue lubricant and is believed to play an important role in regulating the interaction between adjacent tissues. Sodium hyaluronate forms a viscoelastic solution in water, and the high viscosity of sodium hyaluronate solution provides mechanical protection for tissues (iris, retina) and cell layers (cornea, endothelium and epithelium). The elasticity of sodium hyaluronate solution helps absorb mechanical stress and provide protective buffering for tissues. In promoting wound healing, sodium hyaluronate acts as a protective transporter, bringing peptide growth factors and other structural proteins to the site of action, and then enzymatically degrades and releases active proteins to promote tissue repair.

[0005] The active sites on the glycoside ring of the hyaluronic acid main chain are mainly hydroxyl groups with average reactivity, while the carboxyl groups with higher reactivity generally exist in the form of sodium salts, which makes it difficult to modify the material. At present, the modification of the hyaluronic acid main chain generally takes the approach of first activating the hydroxyl groups on the glycoside ring and then reacting with some active substances with specific properties for grafting. However, chemical reaction processes such as grafting lead to lengthy processes and reduce application efficiency; and there are many hydroxyl groups on the main chain, so grafting is random and has poor controllability.

[0006] Oxidized sodium hyaluronate is modified by introducing aldehyde groups into sodium hyaluronate. The reaction is relatively simple and the process controllability is relatively strong. The D-glucuronic acid structure in the main chain of sodium hyaluronate contains two adjacent hydroxyl groups. The two adjacent hydroxyl groups have a certain reducing property. Under the action of the oxidant, the two adjacent hydroxyl groups are oxidized into aldehyde groups, causing the D-glucuronic acid to break the chain and open the ring from the adjacent hydroxyl groups to obtain oxidized sodium hyaluronate containing dialdehyde groups.

[0007] Currently, there is no prior art that studies the application of oxidized sodium hyaluronate with different oxidation degrees in anti-inflammatory or antioxidant aspects, and there is no prior art that discloses how to prepare oxidized sodium hyaluronate with a specific oxidation degree with high yield and stable process.

[0008] Therefore, it is very necessary to develop a method for preparing oxidized sodium hyaluronate that can solve the above technical problems. Summary of the invention

[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing oxidized sodium hyaluronate with high yield and stable process.

[0010] The present invention is achieved through the following technical solutions:

[0011] A method for preparing oxidized sodium hyaluronate comprises the following steps:

[0012] Sodium hyaluronate is added to water, and then a solution containing sodium periodate is added to carry out an oxidation reaction, and ethylene glycol is added to terminate the reaction, and impurities are removed to obtain the product; the molar ratio of sodium hyaluronate to sodium periodate is 1:0.15-3.6;

[0013] The structural formula of the oxidized sodium hyaluronate is as follows, Mw / Mn<3:

[0014]

[0015] In some embodiments of the present invention, the molar ratio of sodium hyaluronate to sodium periodate is 1:0.30-1.5.

[0016] In some embodiments of the present invention, the molar ratio of sodium hyaluronate to sodium periodate is 1:0.38-0.95.

[0017] In some embodiments of the present invention, the molar ratio of sodium hyaluronate to sodium periodate is 1:0.38-0.62.

[0018] In some embodiments of the present invention, the oxidation degree of the oxidized sodium hyaluronate is 10%-98%.

[0019] In some embodiments of the present invention, the oxidation degree of the oxidized sodium hyaluronate is 20%-80%.

[0020] In some embodiments of the present invention, the oxidation degree of the oxidized sodium hyaluronate is 25%-50%.

[0021] In some embodiments of the present invention, the oxidation degree of the oxidized sodium hyaluronate is 25%-45%.

[0022] In some embodiments of the present invention, the oxidation degree of the oxidized sodium hyaluronate is 30%-40%.

[0023] In some embodiments of the present invention, the temperature of the oxidation reaction is 40-70°C.

[0024] In some embodiments of the present invention, the oxidation reaction time is more than 3 hours, preferably 3-6 hours, and more preferably 4-6 hours.

[0025] In some embodiments of the present invention, the impurity removal method is ultrafiltration.

[0026] In some preferred embodiments of the present invention, the ultrafiltration uses an ultrafiltration membrane made of polyethersulfone with a molecular weight cutoff of 1000-30000, preferably 3000-10000.

[0027] In some preferred embodiments of the present invention, the ultrafiltration ends when the conductivity of the effluent is below 10 μS / cm.

[0028] In some more preferred embodiments of the present invention, when the conductivity of the effluent is below 10 μS / cm, water is added to dilute the effluent 5 times or more according to the volume before ultrafiltration, and ultrafiltration is continued and then terminated. The purpose of this operation is to make the ultrafiltration more thorough.

[0029] Among them, the above-mentioned "dilution with water more than 5 times the volume before ultrafiltration" can be a one-time addition of water more than 5 times the volume for dilution, or it can be added in batches, adding a part of water for dilution and then ultrafiltration, then stopping the ultrafiltration, and then adding water for dilution and ultrafiltration, repeating the above process, cumulatively adding water more than 5 times the volume for dilution.

[0030] In some embodiments of the present invention, during the preparation process, the total volume of the feed liquid is controlled to be 28-32 times the volume of the sodium hyaluronate feed amount.

[0031] In some preferred embodiments of the present invention, ultrafiltration is followed by filtration using a 0.45 micron water filter membrane to remove insoluble particles.

[0032] In the present invention, water is used as a solvent to provide a place for the oxidation reaction, so the amount of water is not limited, as long as it can completely dissolve the sodium hyaluronate. However, when the concentration of the sodium hyaluronate solution is too high, it is not conducive to stirring and reaction. Therefore, the mass ratio of sodium hyaluronate to water is preferably above 0.01%.

[0033] In some preferred embodiments of the present invention, the mass ratio of sodium hyaluronate to water is 0.01-5:100, and more preferably 0.025:1.

[0034] In some embodiments of the present invention, the mass concentration of the solution containing sodium periodate is 5-8wt%, preferably 6.23wt%.

[0035] In some embodiments of the present invention, the specific operation of adding sodium hyaluronate to water is: first add sodium hyaluronate to 70-90% of water, then add the remaining water, and stir at 40-70° C. until it is completely dissolved.

[0036] In some embodiments of the present invention, the conditions for terminating the reaction are: after adding ethylene glycol, first keep stirring at 40-70°C for 0.5-1.5h, and then reduce the temperature to 20-30°C.

[0037] In the present invention, the role of ethylene glycol is to terminate the reaction. Therefore, the amount of ethylene glycol used is not limited as long as it can terminate the reaction.

[0038] In some preferred embodiments of the present invention, the volume mass ratio of ethylene glycol to sodium hyaluronate is 0.25 mL:1 g.

[0039] In some embodiments of the present invention, the impurities are removed and then dried. There is no limitation on the drying method, but freeze drying is preferred.

[0040] The beneficial effects of the present invention are:

[0041] The present invention investigates the molar ratio of sodium hyaluronate to sodium periodate, the temperature and reaction time of the oxidation reaction, the impurity removal method and the impurity removal endpoint, and ultimately determines a preparation process of oxidized sodium hyaluronate with a high yield. Moreover, the yield and oxidation degree remain stable after scaled-up production, indicating that the process is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the infrared spectrum of oxidized sodium hyaluronate in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0044] The information of sodium hyaluronate used in the present invention is as follows:

[0045] The structural formula is:

[0046]

[0047] Mw=36.8kDa, Mw / Mn=2.03.

[0048] Example 1

[0049] A method for preparing oxidized sodium hyaluronate comprises the following steps:

[0050] (1) Add 8 g of sodium hyaluronate to 160 mL of water, trying to avoid sticking to the wall; then add 40 mL of water, stir and heat to 60°C, and keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0051] (2) Weigh 0.62 times the amount of sodium periodate (based on the amount of sodium hyaluronate substance), dissolve it in purified water to obtain a sodium periodate solution with a concentration of 6.23 wt %; add it to the sodium hyaluronate aqueous solution, keep it warm at 60° C. and stir for 4 h to react, and obtain a reaction solution.

[0052] (3) Weigh ethylene glycol to a liquid-to-solid ratio of 0.25 mL / g sodium hyaluronate, add it to the reaction solution, stir at 60°C for 1 h, and then cool to 25°C.

[0053] (4) Ultrafiltration was performed using a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 10,000. When the conductivity of the ultrafiltration effluent was below 10 μS / cm, water was added to dilute the effluent to a volume 5 times the volume before ultrafiltration, and ultrafiltration was continued once before termination.

[0054] (5) Pass through a 0.45 μm filter membrane to remove insoluble particles.

[0055] (6) freeze-drying the filtered solution to obtain the product.

[0056] Example 2

[0057] A method for preparing oxidized sodium hyaluronate comprises the following steps:

[0058] (1) Add 5 g of sodium hyaluronate to 35 L of water, trying to avoid sticking to the wall; then add 15 L of water, stir and heat to 70°C, keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0059] (2) Weigh 0.38 times the amount of sodium periodate (based on the amount of sodium hyaluronate substance), dissolve it in purified water to obtain a sodium periodate solution with a concentration of 5 wt %; add it to the sodium hyaluronate aqueous solution, keep it warm at 70° C. and stir for 3 h to react, and obtain a reaction solution.

[0060] (3) Weigh ethylene glycol to a liquid-to-solid ratio of 0.25 mL / g sodium hyaluronate, add it to the reaction solution, stir at 70°C for 0.5 h, and then cool to 20°C.

[0061] (4) Ultrafiltration was performed using a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 3000. When the conductivity of the ultrafiltration effluent was below 10 μS / cm, water was added to dilute the effluent to a volume 5 times the volume before ultrafiltration, and ultrafiltration was continued once before termination.

[0062] (5) Pass through a 0.45 μm filter membrane to remove insoluble particles.

[0063] (6) freeze-drying the filtered solution to obtain the product.

[0064] Example 3

[0065] A method for preparing oxidized sodium hyaluronate comprises the following steps:

[0066] (1) Add 5 g of sodium hyaluronate to 90 mL of water, trying to avoid sticking to the wall; then add 10 mL of water, stir and heat to 40°C, and keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0067] (2) Weigh 0.95 times the amount of sodium periodate (based on the amount of sodium hyaluronate substance), dissolve it in purified water to obtain a sodium periodate solution with a concentration of 8 wt %; add it to the sodium hyaluronate aqueous solution, keep it warm at 40° C. and stir for 6 h to react, and obtain a reaction solution.

[0068] (3) Weigh ethylene glycol to a liquid-to-solid ratio of 0.25 mL / g sodium hyaluronate, add it to the reaction solution, stir at 40°C for 1.5 h, and then cool to 30°C.

[0069] (4) Ultrafiltration was performed using a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 1000. When the conductivity of the ultrafiltration effluent was below 10 μS / cm, water was added to dilute the effluent to a volume 5 times the volume before ultrafiltration, and ultrafiltration was continued once before termination.

[0070] (5) Pass through a 0.45 μm filter membrane to remove insoluble particles.

[0071] (6) freeze-drying the filtered solution to obtain the product.

[0072] Example 4 Process Conditions Investigation

[0073] 4.1 Investigation of the dosage of sodium periodate

[0074] The difference from Example 1 is only that the amount of sodium periodate is different, and the other conditions are the same. The results are shown in Table 1.

[0075] Table 1 Investigation of sodium periodate dosage

[0076]

[0077] Results and analysis: According to the experimental results, as the dosage of sodium periodate gradually increases, the oxidation degree of the product is between 11.35% and 98.46%.

[0078] 4.2 Investigation of reaction temperature

[0079] The only difference from Example 1 is the reaction temperature in step (2), and the other conditions are the same. The results are shown in Table 2.

[0080] Table 2 Investigation of reaction temperature

[0081]

[0082] Results and analysis: According to the experimental results, the oxidation degree of the reaction product at 30℃ was significantly reduced, the oxidation degree of the reaction product at 40℃-70℃ was within the range of 40±3%, and the oxidation degree of the product obtained at 80℃ was 41.79%, but the yield was significantly lower than that of other groups, which may be related to product degradation caused by excessively high temperature; therefore, the final reaction temperature was confirmed to be 40-70℃.

[0083] 4.3 Investigation of reaction time

[0084] The only difference from Example 1 is the reaction time in step (2), and the other conditions are the same. The results are shown in Table 3.

[0085] Table 3 Investigation of reaction time

[0086]

[0087]

[0088] Results and analysis: According to the experimental results, it is proved that a relatively suitable oxidation degree can be achieved in a reaction time of 3-6 hours, and extending the reaction time for more than 4 hours will not affect the product quality.

[0089] 4.4 Investigation of impurity removal methods

[0090] The impurity removal method is crucial to the quality of the product. Ultrafiltration, nanofiltration, and dialysis bag dialysis were performed by trying different materials (polyethersulfone, cellulose, and polyamide) and molecular weight cutoffs (30,000, 10,000, 5,000, 1,000, and 800) to remove the introduced sodium periodate (periodic acid and iodic acid), and the yield and quality of the product were compared. The results are shown in Table 4. The different impurity removal methods in Table 4 are all performed on the basis of step (4) of Example 1, and the other conditions are the same as those of Example 1.

[0091] Table 4 Investigation of impurity removal methods

[0092]

[0093] Results and analysis: According to the results in the above table, the nanofiltration desalination yield is relatively low; ultrafiltration method: the molecular weight cutoff of polyethersulfone material is 30,000, 10,000, 5,000, and 1,000, and the product yield is relatively high; the dialysis bag has the highest yield, but it takes a long time and is affected by the specifications of the dialysis bag and cannot be scaled up in large quantities; neither periodic acid nor iodic acid was detected.

[0094] Therefore, it was finally decided to use ultrafiltration to remove impurities. The filter bag material is polyethersulfone and the retention molecular weight is 1000-30000.

[0095] 4.5 Investigation of ultrafiltration control endpoint

[0096] The only difference from Example 1 is that the ultrafiltration endpoint is different, that is, the conductivity of the effluent is different, as shown in Table 5, and the other conditions are the same.

[0097] Table 5 Investigation of ultrafiltration control end point

[0098] Code / Batch No. Amount of material Conductivity of effluent Ethylene glycol (limit 0.062%) Periodic acid and sodium iodate 20210501-1 1.24g 55.2μS / cm 0.113% 0.01% 20210501-2 1.36g 40.3μS / cm 0.152% 0.02% 20210501-3 1.20g 20.8μS / cm 0.031% Not detected 20210501-4 1.37g 18.7μS / cm 0.005% Not detected 20210501-5 1.20g 9.2μS / cm Not detected Not detected

[0099] Example 5 Process Scale-up Investigation

[0100] 5.1 Sodium hyaluronate dosage 80g

[0101] The difference from Example 1 is only that the amount of sodium hyaluronate and the amount of water used in step (1) are different, and the other conditions are the same. The details are as follows:

[0102] (1) Add 1.6 L of purified water to the reactor and slowly add 80 g of sodium hyaluronate while stirring, trying to avoid sticking to the wall; then add 0.4 L of purified water, stir and heat to 60° C. and keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0103] 5.2 Sodium hyaluronate dosage: 160g

[0104] The difference from Example 1 is only that the amount of sodium hyaluronate and the amount of water used in step (1) are different, and the other conditions are the same. The details are as follows:

[0105] (1) Add 3.2 L of purified water to the reactor and slowly add 160 g of sodium hyaluronate while stirring, trying to avoid sticking to the wall; then add 0.8 L of purified water, stir and heat to 60° C. and keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0106] 5.3 Sodium hyaluronate dosage 700g

[0107] The difference from Example 1 is only that the amount of sodium hyaluronate and the amount of water used in step (1) are different, and the other conditions are the same. The details are as follows:

[0108] (1) 14 L of purified water was added to the reaction kettle, and 700 g of sodium hyaluronate (1.74 mol) was slowly added while stirring, trying to avoid sticking to the wall; then 3.5 L of purified water was added, and the mixture was heated to 60° C. and stirred until it was completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0109] The above products were tested, and the test results are shown in Table 6.

[0110] Table 6 Process scale-up investigation results

[0111]

[0112] Note: Weight yield (%) = amount of material obtained / amount of material added*100%.

[0113] According to the results in the above table, the optimized process is used for process scale-up, and the results are relatively ideal. The yield is relatively stable, and the degree of oxidation is maintained at about 40%, indicating that it is suitable for industrial scale-up production.

[0114] Example 6

[0115] The feed amounts in Example 2, Example 3 and some investigation tests were all increased to 700 g, and process scale-up investigation was conducted. The results are shown in Table 7.

[0116] The difference between the enlarged process of Example 2 and Example 2 is only the difference in the amount of sodium hyaluronate and the amount of water used in step (1), and the other conditions are the same. 3 Add 700g of sodium hyaluronate to the water, try to avoid sticking to the wall; then add 2.1m 3 water, stir and heat to 70°C, keep stirring until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0117] The difference between the enlarged process of Example 3 and Example 3 is only that the amount of sodium hyaluronate and the amount of water used in step (1) are different, and the other conditions are the same. Specifically, 700g of sodium hyaluronate is added to 12.6L of water, and it is avoided to stick to the wall as much as possible; then 1.4L of water is added, and the temperature is raised to 40°C and stirred until it is completely dissolved to obtain a sodium hyaluronate aqueous solution.

[0118] Step (1) in the scaled-up process of some investigation experiments is the same as that in Example 5.3, and the other conditions remain unchanged.

[0119] Table 7 Process scale-up oxidation degree results

[0120]

[0121] Test Example 1 Infrared Test

[0122] The infrared spectrum of the oxidized sodium hyaluronate prepared in Example 1 is as follows: Figure 1 shown.

[0123] Test Example 2 Anti-inflammatory Test

[0124] The inflammatory response of human immortalized epidermal cells (HaCaT) induced by interleukin IL-1β was used as a model to verify that the oxidized hyaluronic acid in the present invention has an anti-inflammatory effect.

[0125] Human immortalized epidermal cells (HaCaT) were cultured at 5×10 3 cells / mL, 100 μL per well was inoculated in a 96-well plate, 6 replicates were set for each group, and after culturing for 24 hours, the culture medium containing 10 ng / mL interleukin IL-1β and 20 mg / mL oxidized sodium hyaluronate in Example 1 or other investigation tests was replaced, and the cells without IL-1β and oxidized sodium hyaluronate were used as the normal control group, and the cells with only IL-1β but no oxidized sodium hyaluronate were used as the model control group. After continuing to culture for 24 hours, the expression levels of interleukin IL-1α and tumor necrosis factor TNF-α were detected using an ELISA kit. The test results are shown in Table 8.

[0126] Table 8 Anti-inflammatory effect

[0127] Group IL-1α (ng / mL) TNF-α(ng / mL) Normal control group 44.27 1.83 Model control group 315.12 4.39 Example 1 68.17 1.89 20210302 122.3 2.65 20210301 131.4 2.81 20210309 103.8 2.34 20210310 99.5 2.09

[0128] It can be seen from the data in the above table that the oxidized sodium hyaluronate of Example 1 can reduce the expression levels of IL-1α and TNF-α in cells and has a certain anti-inflammatory effect.

[0129] Test Example 3 Antioxidant Test

[0130] (1) DPPH free radical scavenging test

[0131] The antioxidant properties of the hydrogel were evaluated by the 1,1-diphenyl-2-picrylhydrazyl free radical (DPPH) method. DPPH was dissolved in anhydrous ethanol at a concentration of 200 μM under light protection. Then 10 mg of the material in Example 1 or other investigation tests was dissolved in 2 mL of ultrapure water, and mixed with the above DPPH solution in a ratio of 1:1 (v:v). After mixing evenly, incubate at 37 ° C in the dark for 4 hours. At the same time, ethanol: water = 1:1 was used as a blank experimental group. Finally, the absorbance of the solution after the reaction at 517 nm was measured by a UV spectrophotometer. Each material was tested in parallel 3 times and the average value was taken. The test is shown in Table 9.

[0132] (2) ABTS + Free Radical Scavenging Test

[0133] ABTS + Dissolve in ultrapure water to prepare 7.4 mM ABTS. +In addition, weigh K2S2O8 and prepare a 2.6mM solution with ultrapure water. Mix the two solutions at a ratio of 1:1 (v:v). Mix them evenly and react at room temperature in the dark for 12 hours. After the reaction is completed, dilute the mixed reaction solution 50 times with PBS solution with a pH of 7.4 as ABTS· + Working solution, finally, the sample solution was mixed at a ratio of 1:4, and the absorbance of the solution after the reaction was measured at 734nm using a UV spectrophotometer. At the same time, a PBS solution with a pH of 7.4 was used as a blank experimental group, and each material was tested in parallel 3 times, and the average value was taken. The test is shown in Table 9.

[0134] Table 9 Antioxidant activity test results

[0135]

[0136]

[0137] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A method for preparing oxidized sodium hyaluronate, characterized in that: The steps include: Sodium hyaluronate is added to water, and then a solution containing sodium periodate is added to carry out an oxidation reaction, and ethylene glycol is added to terminate the reaction, and impurities are removed to obtain the product; the molar ratio of sodium hyaluronate to sodium periodate is 1:0.15-3.6; The structural formula of the oxidized sodium hyaluronate is as follows:

2. The preparation method according to claim 1, characterized in that: The temperature of the oxidation reaction is 40-70° C., and the time of the oxidation reaction is more than 3 hours.

3. The preparation method according to claim 1, characterized in that: The molar ratio of sodium hyaluronate to sodium periodate is 1:0.30-1.

5.

4. The preparation method according to claim 3, characterized in that: The molar ratio of sodium hyaluronate to sodium periodate is 1:0.38-0.

95.

5. The preparation method according to claim 4, characterized in that: The molar ratio of sodium hyaluronate to sodium periodate is 1:0.38-0.

62.

6. The preparation method according to claim 1, characterized in that: The oxidation degree of the oxidized sodium hyaluronate is 10%-98%.

7. The preparation method according to claim 6, characterized in that: The oxidation degree of the oxidized sodium hyaluronate is 20%-80%.

8. The preparation method according to claim 7, characterized in that: The oxidation degree of the oxidized sodium hyaluronate is 25%-50%.

9. The preparation method according to claim 1, characterized in that: The impurity removal method is ultrafiltration.

10. The preparation method according to claim 9, characterized in that: The ultrafiltration uses an ultrafiltration membrane made of polyethersulfone with a molecular weight cutoff of 1000-30000.

11. The preparation method according to claim 10, characterized in that: The ultrafiltration uses an ultrafiltration membrane made of polyethersulfone with a molecular weight cutoff of 3000-10000.

12. The preparation method according to claim 9, characterized in that: The ultrafiltration was terminated when the conductivity of the effluent was below 10 μS / cm.

13. The preparation method according to claim 12, characterized in that: When the conductivity of the effluent is below 10 μS / cm, dilute it with water 5 times or more of the volume before ultrafiltration, and continue ultrafiltration until it is terminated.

14. The preparation method according to claim 1, characterized in that: The mass ratio of sodium hyaluronate to water is above 0.01%; the mass concentration of the solution containing sodium periodate is 5-8wt%.

15. The preparation method according to claim 1, characterized in that: The specific operation of adding sodium hyaluronate to water is: first add sodium hyaluronate to 70-90% of water, then add the remaining water, and stir at 40-70° C. until it is completely dissolved.

16. The preparation method according to claim 1, characterized in that: The conditions for terminating the reaction are as follows: after adding ethylene glycol, the mixture is stirred at 40-70°C for 0.5-1.5h and then cooled to 20-30°C.

Citation Information

Cited By

  • High-viscosity antibacterial hydrogel dressing as well as preparation method and application thereof

    CN121221838A